THE FUNCTIONS AND THE SYMBOLIC MEANING OF PENTI TRADITION FOR THE COMMUNITY OF PERAK VILLAGE, CIBAL DISTRICT, MANGGARAI REGENCY-NTT - Abon, Felisitas Alsiana; Sucipto; Imayah (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
This study aims to explain the function of the penti tradition in the Manggarai community of Perak village and describe the symbolic meaning of the penti tradition in the Manggarai village of Perak. This type of qualitative descriptive research. The data sources used are primary data sources and secondary data sources. Data collection techniques used are observation, interviews and documentation. The data analysis method used is data collection, data reduction, data presentation, and conclusions. The data validity method used is source triangulation. The results obtained from the function of the penti tradition are asking for soil fertility before Mori Jari Dedek (God the Creator) and the penti ceremony as social solidarity. While the meaning of the penti tradition symbols are barong wae (spring source), takung pa'ang (respect to the village gatekeeper), compang takung (a place to store offerings), teing hang one mbaru gendang (giving offerings to ancestors), and penti (thanksgiving).